Serum proteases alter the antigenicity of peptides presented by class I major histocompatibility complex molecules. - Falo, L D (1992)
Any effect of serum on the antigenicity of peptides is potentially relevant to their use as immunogens in vivo. Here we demonstrate that serum contains distinct proteases that can increase or decrease the antigenicity of peptides. By using a functional assay, we show that a serum component other than beta 2-microglobulin enhances the presentation of ovalbumin peptides produced by cyanogen bromide cleavage. Three features of this serum activity implicate proteolysis: it is temperature dependent, it results in increased antigenicity in a low molecular weight peptide fraction, and it is inhibited by the protease inhibitor leupeptin. Conversely, presentation of the synthetic peptide OVA-(257-264) is inhibited by serum. This inhibition is unaffected by leupeptin but is blocked by bestatin, a protease inhibitor with distinct substrate specificities. Implications for peptide-based vaccine design and immunotherapy are discussed.